Development of a novel fungal fluidized-bed reactor for gaseous ethanol removal. (April 2020) - Lu, Lichao; Dong, Dong; Baig, Zenab Tariq; Yeung, Marvin; Xi, Jinying
Abstract: Fluidized bed bioreactors can overcome the limitations of packed bed bioreactors such as clogging, which has been observed in the industrial application for decades. The key to establish a gaseous fluidized bed bioreactor for treatment of volatile organic compounds is to achieve microbial growth on a light packing material. In this study, Two fungal species and two bacterial species were isolated to build a fungal fluidized-bed reactor (FFBR). A light packing material with wheat bran coated on expended polystyrene was used. The FFBR was operated for 65 days for gaseous ethanol removal and obtained elimination capacities of 500–1800 g∙m −3 ∙h −1 and removal efficiencies of 20-50%. The pressure drops was well controlled with values around 400 Pa∙m −1 . Stress tolerant genera including Aureobasidium, Stenotrophomonas and Brevundimonas were dominant. Meyerozyma, whose species were present in an initial inoculated isolate, was detected among the dominant species with 28.70% relative abundance; they were reported to degrade complicated compounds under similarly stressful environments. Highlights: A novel fungal fluidized bed reactor (FFBR) was successfully developed. Four isolates, including Meyerozyma guilliermondii, was inoculated. High ethanol removal capacity up to 1800 g h −1 ∙m −3 was achieved.